Collaboration Between Regencies in Fulfilling The National Production of Rajangan Madura Tobacco - Dzikrillah Thoriqur Rahman; Retno Sunu Astuti (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study tries to analyze the concept of inter-regency in the fulfillment of the national production of Madura shredded tobacco and study the factors that cause the decline in Madura sliced tobacco production. Problems that arise at the time of production as well as the area of agricultural tobacco in each district besides the instability of tobacco prices which causes anxiety for farmers. To discuss this problem, reference theory from Wright (1974) in Irawanto et al. 2015: 20) there are five key elements in the implementation of intergovernmental relations, i.e. 1) the role of government, 2) interaction of public officials, 3) sustainability communication, 4) the role of administrators, and 5) focus of attention on policy. Data collected through observation, interviews (FGD) and literature study and analyzed qualitatively descriptive. This study represents collaboration between districts which has shown good collaboration by dividing the roles of each region. Interaction of public officials has proven participation in interactions, beliefs, perceptions and preferences. With regard to communication developed from four regions looking for ways and solutions to increase Madura tobacco production and avoid the volatility of Madura shredded tobacco prices in the harvest season. This collaboration has a target of achieving fulfillment of Madura Chopped Tobacco Production, increasing thirty percent from Madura Tobacco Production annually targeting eighty tons.